2022
DOI: 10.1190/int-2021-0193.1
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic seismic data for training deep learning networks

Abstract: Deep learning is increasingly being used as a component of geoscience workflows for processing and interpreting seismic data. Training a supervised deep learning network is a data-hungry task: Lots of data examples are needed and they must include labels. The data examples and their labels must have consistent patterns for the deep learning network to learn. Too few examples and/or poor-quality labels can lead to poor deep learning training results. One method to provide large quantities of training examples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Deep learning has been used for seismic signal processing (Baardman & Hegge, 2021; Vinard et al., 2022; Yu et al., 2019; Wang et al., 2020), imaging and inversion (Aleardi & Salusti, 2021; Roethe & Tarantola, 1991; Ruiz et al., 2021; Sun et al., 2020; Wang et al., 2021; Zhang & Alkhalifah, 2019; Zhang & Gao, 2021) and seismic data interpretation (Durall et al., 2021; Duan et al., 2019; Grana et al., 2020; Li et al., 2020; Merrifield et al., 2022; Tschannen et al., 2020; Vizeu et al., 2022; Wu et al., 2020). Existing studies have shown that training datasets play an important role in deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning has been used for seismic signal processing (Baardman & Hegge, 2021; Vinard et al., 2022; Yu et al., 2019; Wang et al., 2020), imaging and inversion (Aleardi & Salusti, 2021; Roethe & Tarantola, 1991; Ruiz et al., 2021; Sun et al., 2020; Wang et al., 2021; Zhang & Alkhalifah, 2019; Zhang & Gao, 2021) and seismic data interpretation (Durall et al., 2021; Duan et al., 2019; Grana et al., 2020; Li et al., 2020; Merrifield et al., 2022; Tschannen et al., 2020; Vizeu et al., 2022; Wu et al., 2020). Existing studies have shown that training datasets play an important role in deep learning.…”
Section: Introductionmentioning
confidence: 99%